Implementasi Strategi Peningkatan Kompetensi Sumber Daya Aparatur pada Badan Kepegawaian Daerah Kabupaten Karo Provinsi Sumatera Utara - Yunia Sarah; Adil Mubarak (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to determine the implementation of a strategy to increase the competence of Apparatus Resources at the Regional Personnel Agency of Karo Regency, North Sumatra Province. This research was conducted using a qualitative descriptive research method, the withdrawal of informants using a purposive sampling technique. Thus, the data was collected using interviews, observation, and documentation studies. Data analysis is done by reducing, presenting, and drawing conclusions. Then the validity of this data was tested by triangulation of sources and analyzed. In conclusion, the strategy implementation to increase the competence of Apparatus Resources at the Regional Personnel Agency of Karo Regency, North Sumatra Province, has not run optimally. The cause is that the overall implementation indicators have not been met because participants do not focus on understanding the material when the activity is running. In contrast, some of the obstacles that become obstacles are the limited number of personnel and improper time management in carrying out activities, as well as the lack of enthusiasm and desire of employees to participate in activities and budget constraints from the local government, which results in delays. In the distribution of activity funds.